Retrospective Analysis of Skull and Spine Traumas - Kaya, Büşra Betül; Özdemir, Fikri; Gümüş, Burak; Komut, Erdal (The Bulletin of Legal Medicine, 2023)
Objective: In this study, in patients who applied to the forensic medicine outpatient clinic due to skull and spine trauma; We aimed to compare categorical data by defining age, gender, causes of trauma, trauma site, fracture type and accompanying pathologies. Methods: Files and computed tomography reports of a total of 105 patients, 24 women and 81 men, between the ages of 18 and 75, who were exposed to skull and spine trauma, registered in the database of the Hitit University Erol Olçok Training and Research Hospital Forensic Medicine Polyclinic Unit between 01.01.2017 and 31.12.2020 examined. In cases; gender, age, cause of trauma, fracture type, injury site, multiple site injuries and presence of pathologies accompanying trauma were evaluated. Data analysis was performed with the IBM SPSS Statistics 22.0 statistical program. Categorical data were compared with chi-square and Fisher Exact tests. Results: The most trauma was detected in male individuals aged 51-60 years. The most common cause of trauma was traffic accidents with a rate of 48.6% (51 cases). In the skull, frontal linear fractures and in the spine, lumbar vertebrae corpus fractures were the most common lesions. Pneumocephaly, spinal injuries and paraplegia were seen as a complication. Conclusion: We think that our study will be beneficial in terms of guiding physicians in the observation, diagnosis and reporting processes of patients who apply to the Forensic Medicine units of hospitals.